Impact of Stem Size on Turbulence and Sediment Resuspension Under Unidirectional Flow. Issue 3 (9th March 2021) - Liu, Chao; Shan, Yuqi; Nepf, Heidi
Abstract: Laboratory experiments examined the impact of model vegetation on turbulence and resuspension. The turbulent kinetic energy increased with increasing velocity and increasing solid volume fraction, but did not depend on stem diameter. The vegetation‐generated turbulence dominated the total turbulence inside canopies. For the same sediment size, the critical turbulent kinetic energy at which resuspension was initiated was the same for both vegetated and bare beds, which resulted in a critical velocity that decreased with increasing solid volume fraction. Both the critical turbulence and critical velocity for resuspension had no dependence on stem diameter. However, for denser canopies and/or a canopy of smaller stem size, a greater energy slope is required to initiate resuspension. This study provides a way to predict the onset of resuspension in regions with vegetation, an important threshold for sediment transport and landscape evolution. Plain Language Summary: Vegetation‐generated turbulence plays an important role in sediment resuspension, which may impact the evolution of vegetated landscapes. In nature, aquatic vegetation includes a large number of species and each has a specific range of stem diameter. The goal of this study was to investigate the influence of stem diameter on vegetation‐generated turbulence and resulting resuspension inside emergent canopies. First, laboratory experiments showed that turbulence increased monotonically with increasing velocity and with increasing vegetation density. Second, the critical turbulence and critical velocity required to trigger resuspension were defined when the measured concentration of suspended sediment exceeded the background noise. The critical turbulence was the same in both vegetated and bare channels, but the critical velocity decreased with increasing vegetation density. The influence of vegetation diameter on turbulence and resuspension was negligible. However, for denser canopies and/or a canopy of smaller stem size, a greater bed slope and/or water surface slope is required to initiate resuspension. This study provides a way to predict the onset of resuspension in regions with vegetation, an important threshold for sediment transport and landscape evolution. Key Points: For the same solid volume fraction and velocity, the stem diameter has a negligible influence on turbulence magnitude and resuspension The critical velocity for resuspension decreases with increasing solid volume fraction and has no dependence on stem diameter For a denser canopy and/or a canopy of smaller stem size, a greater energy slope is required to initiate resuspension